KISAH NABI NUH DALAM AL-QUR’AN (PENDEKATAN INTERTEKSTUAL JULIA KRISTEVA) - Khikmatiar, Azkiya (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2019)
This article discusses the story of Noah in the Qur'an. As a story contained in the Qur'an and the Bible, the story of Noah is very important to find the the differences between them. Therefore, the used approach  is intertextuality initiated by Julia Kristeva who tried to compare two narrations. By using this approach , we found many differences. In the structure of narration, al-Qur?an does many simplifications, so that the haplological principle becomes dominant in each fragment. However, in other fragments other principles are also found such as existence, modification, and conversion. The most basic difference between them is in theme of the story. The story of Noah in the Qur'an has monotheism or tauhid theme, while in the Bible the theme is human crime.